Truth for a truth - Richards, Emilie (Waterville, Me. Thorndike Press, 2011)
After Godwin "Win" Dorchester, a former minister of the Consolidated Community Church, dies suddenly during a celebration of his return to Emerald Springs, his memorial service is cut just as short. The coroner's office has requested an autopsy, and minister's wife Aggie Sloan-Wilcox is the first to learn why. Win, beloved among the congregation, was murdered - and the number one suspect is his widow. Hildy Dorchester may be meddlesome, but Aggie knows her predecessor, a relentless do-gooder, isn't a killer.
97963
Keywords: Sloan-Wilcox, Aggie (Fictitious character); Spouses of clergy; Murder -- Investigation; Large type books; Ohio; Mystery fiction